2005
DOI: 10.1117/12.606807
|View full text |Cite
|
Sign up to set email alerts
|

CD reference features with sub-five nanometer uncertainty

Abstract: The implementation of a new test structure for HRTEM (High-Resolution Transmission Electron Microscopy) imaging, and the use of CD AFM (CD Atomic Force Microscopy) to serve as the transfer metrology, have resulted in reductions in the uncertainties attributed to critical dimension (CD) reference-material features, having calibrated CDs less than 100 nm. The previous generation of reference materials, which was field-tested in 2001, used electrical CD as the transfer metrology. Calibrated CD values were in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…As a result of the NIST SCCDRM project, it is possible to calibrate the zeroth order tip width with approximately a 1 nm standard uncertainty. 5,[11][12][13] The finer details of the tip-sample interaction, pertaining to things like flare radius, offset height, feature sidewall angle, feature corner radius, and the three-dimensional nature of both the tip and sample (i.e., shape in the axis perpendicular to the scan direction) are thought of as being higher-order tip effects. 5 Because these effects have a strong dependence on the specific geometry of each tip and feature, it is difficult to make general statements about the resulting uncertainties, and it is necessary to make a specific assessment for every measurement.…”
Section: The Nist Cd-afmmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the NIST SCCDRM project, it is possible to calibrate the zeroth order tip width with approximately a 1 nm standard uncertainty. 5,[11][12][13] The finer details of the tip-sample interaction, pertaining to things like flare radius, offset height, feature sidewall angle, feature corner radius, and the three-dimensional nature of both the tip and sample (i.e., shape in the axis perpendicular to the scan direction) are thought of as being higher-order tip effects. 5 Because these effects have a strong dependence on the specific geometry of each tip and feature, it is difficult to make general statements about the resulting uncertainties, and it is necessary to make a specific assessment for every measurement.…”
Section: The Nist Cd-afmmentioning
confidence: 99%
“…As a result of the NIST single crystal critical dimension reference material (SCCDRM) project, it is possible to calibrate CD-AFM tip width with a 1 nm standard uncertainty. 5,[11][12][13] And we are now using the SXM320 to support the next generation of the SCCDRM project, which may lead to even lower uncertainties.…”
Section: Introductionmentioning
confidence: 98%
“…These overall results of the project are being described elsewhere. 9 Therefore, the rest of this discussion will focus on the AFM methodology that was used, and the application of the SCCDRM samples to AFM linewidth metrology.…”
Section: Application Of the Cd-afm Rms To The Sccdrm Projectmentioning
confidence: 99%
“…The details of our analysis are being reported elsewhere. 9 The HRTEM fringes were counted manually and the images were analyzed in detail. Based upon this analysis, we concluded that most potential biases pertaining to sample preparation (e.g., surface effects, membrane distortion, FIB-induced damage) were not a concern.…”
Section: Traceability and Validating Metrologymentioning
confidence: 99%
See 1 more Smart Citation